Asymmetries between because and for reason clauses: Licensing speaker perspective - de Vos, Mark (Nordlyd, 2026)
Although English because and for appear to be near-synonymous causal connectives, this paper shows that for has a distinct grammatical and semantic profile. When for introduces finite clauses, they are extraposed and inaccessible for syntactic processes. This contrasts with when for introduces non-finite gerundive adjuncts which behave like ordinary adjuncts; the interpretive range is narrower and less straightforwardly causal. I then identify an unexpected asymmetry in the scope of finite for and because clauses: foris often restricted to matrix clause interpretation, while because readily allows both matrix and embedded scope. I argue that finite for always licenses an explicit discourse-speaker point of view evaluation. Building on this, I propose an analysis in which for is semantically underspecified, assigns a generalized GROUND theta role (Talmy 1978; 2000) to a Discourse Speaker Point of View projection (Speas and Tenny 2003, Miyagawa 2012). In addition for possesses interpretable but unvalued features in the senseof Pesetsky and Torrego (2007) within its lexical specification. The interaction of theta-role assignment and feature checking derives the observed distributional and interpretive properties and suggests a unified lexical entry of for across its complementizer and prepositional uses.
Keywords: clausal adjuncts; Causal Conjunctions; syntax-semantics interface